Research and teaching activity in UK occupational physicians. (23rd October 2019) - Lalloo, D; Demou, E; Pahl, N; Macdonald, E B
Abstract: Background: For all doctors, including occupational physicians (OPs), research and teaching are considered core requirements of medical education and continuing professional development. Academic skills are also vital to evidence-based practice and advancement of occupational health (OH) as a specialty. In recent years, attention has focussed on the declining UK OH academic base and the research– practice gap, and increased practitioner participation in research is encouraged. Aims: To establish a baseline of research and teaching activity among UK OPs, identify related barriers and inform strategies to overcome them. Methods: An online survey including specific career profile questions derived from consensus following expert panel discussions. It formed part of a larger Delphi study on UK OH research priorities. Results: We received 213 responses, about 18% of 1207 practising UK OPs. Of these, 162 (76%) undertook research at some career-point, of which 44 (27%) were currently research-active. Similarly, 154 (72%) undertook teaching at some career-point, of which 99 (64%) were currently teaching-active. Of those who had never undertaken research ( n = 51) or teaching ( n = 59), 40 and 42% were interested in doing so, respectively. Key barriers were lack of time and opportunity, the former particularly for respondents practising in industry, where 'commercial' demands take priority, rather than healthcare. Conclusions: This study establishes a benchmark of academic activity among UK OPs and identifies related barriers. These 'target' barriers can shape research funding priorities and education to increase participation and develop the UK OH academic base.